The feminine uncanny: Olimpia and other imaginary ghostly female faces - Abalia Marijuán, Andrea (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Art and the Uncanny are linked in the aesthetic that explores the limits of unconscious desire, there where the sinister feeling is experienced. Although there are various causes that have long ago brought out this disturbing and attractive sensation, women have been undoubtedly one of the issues that has raised it. Its uncanny potential arises as a result of a patriarchal society that has negativized its differential condition from the dominant gender. Thus, since Greek myths like Galatea or Medusa, passing through the famous automatons of Romanticism such as Hoffmann's Olimpia, the image of women along literary and visual arts has been based on sinister fantasies of domination. The present article aims to rescue and analyse these and other misogynist imaginary figures in order to clarify the causes of the feminine uncanny with a gender perspective.
Keywords: uncanny; feminine; Olimpia; misoginy; Romanticism; dead woman